A possible relationship between Thromboxane B2 and Leukotriene B4 and the encapsulation of Dirofilaria repens worms in human subcutaneous dirofilariasis. (2020) - Morchón, R.; Carretón, E.; García, R.; Zueva, T.; Kartashev, V.; Simón, F.
Abstract: Human subcutaneous dirofilariosis has several clinical presentations. Many cases present as subcutaneous nodules, as a consequence of a local inflammatory reaction that encapsulates and destroys the worms. In addition, there are cases in which migrating worms located in the ocular area remain unencapsulated. In the present work, the levels of two pro-inflammatory eicosanoids, thromboxane B2 (TxB2) and leukotriene B4 (LTB4) are analysed by commercial Enzime-Linked immunosorbent assay (ELISA) in serum samples from 43 individuals, 28 diagnosed as having subcutaneous dirofilariasis presenting a subcutaneous nodule, five diagnosed as having dirofilariasis, in which the worms remained unencapsulated in the periphery of the eye, and ten healthy individuals living in a non-endemic area, used as controls. The worms were surgically removed, identifying Dirofilaria repens as the causative agent in all cases, by Polymerase Chain Reaction (PCR). Individuals with nodules showed significantly higher levels of TxB2 and LTB4 than healthy controls, whereas significant differences in LTB4 levels were observed between individuals with unencapsulated worms and healthy controls. It is speculated that the absence of LTB4 may contribute to the fact that worms remain unencapsulated as a part of immune evasion mechanisms.